2007
DOI: 10.1080/10641950701436016
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Adaptation during Pregnancy in Chronic Hypertension

Abstract: The hemodynamics of chronic hypertension during pregnancy are characterized by persistent high vascular resistance. Lower SI and NT-proANP values found in chronic hypertensive pregnancies during the early second trimester may suggest a reduced intravascular volume increase during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…No significant difference between treated and untreated women could be detected. Previous trials reported conflicting results whether chronic hypertension impacts fetal outcome [ 29 , 30 ]. However, the difference in birthweight seems much more pronounced than in gestational age, which may indicate a growth restriction in these pathologies independent of gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference between treated and untreated women could be detected. Previous trials reported conflicting results whether chronic hypertension impacts fetal outcome [ 29 , 30 ]. However, the difference in birthweight seems much more pronounced than in gestational age, which may indicate a growth restriction in these pathologies independent of gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…; Tihtonen et al. ). In dogs, increases in ANP have been described as a response to increased atrial volume (Paganelli et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Tihtonen et al. ; Abbott ; Blanco et al. ); and abnormalities related to ventricular change and pulmonary hypertension correlate with the levels of NT‐proBNP (Yoshimura et al.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Pregnancies complicated by HDP are generally characterized by a significantly increased left ventricular mass, [26][27][28][29][30][31] concentric hypertrophy, 27,28,32 and increased SVR 13,26,30,31,33 compared with normotensive pregnancy. Specifically, pregnant women with chronic hypertension are characterized by persistent high SVR and reduced intravascular volume expansion throughout pregnancy compared with normotensive pregnancy 34 ; while evidence on cardiovascular changes in gestational hypertension is conflicting. 13,22,26,30,33,35,36 Stroke volume and myocardial performance index are expected to be reduced in pre-eclampsia compared with normotensive pregnancy.…”
Section: Cardiovascular Changes In Women With Hypertensive Disorders ...mentioning
confidence: 99%